Comparison of radiation exposure to physicians between anteroposterior and lateral real-time fluoroscopy when performing lumbar transforaminal epidural steroid injections: A randomized controlled trial. Issue 27 (8th July 2022) - Yoo, Seung Hee; Kim, Won-Joong; Jue, Mi Jin; Lee, Min Jin
Abstract : Background: Lumbar transforaminal epidural steroid injections are used widely to alleviate low back radicular pain, but it requires real-time fluoroscopy, which can increase the risk of radiation exposure. Anteroposterior or lateral real-time fluoroscopy can be used during lumbar transforaminal epidural steroid injections, but there have been no comparative studies on the exposure of physicians to radiation from anteroposterior or lateral real-time fluoroscopy. The aim of this study was to compare the cumulative radiation exposure to each body part of the physician according to the method of real-time fluoroscopy when performing lumbar transforaminal epidural steroid injections. Methods: A single physician performed lumbar transforaminal epidural steroid injections, and 2 groups of patients were formed based on the method used: group A (anteroposterior real-time fluoroscopy) and group L (lateral real-time fluoroscopy). Dosimeters were placed outside the chest, inside the chest, outside the thyroid collar, inside the thyroid collar, outside the groin, inside the groin, outside the lead gloves, and left rim of the glasses. Results: A total of 200 lumbar transforaminal epidural steroid injections were analyzed, and the radiation exposure was measured by cumulative dose equivalents in mSv. The dose equivalents were lower at every level in group A compared with group L except for outside the groin. Conclusions: The cumulative radiation exposure at all the measurement sites was lower for anteroposterior real-time fluoroscopy compared with lateral real-time fluoroscopy when performing lumbar transforaminal epidural steroid injections, except for outside the groin.